The Relationship Between Personal Hygiene And The Severity of Acne Faculty of Medicine, Prima Indonesia University Year 2025 - Indri Nabilah Bancin; Dewi Sartika; Masdalena Nasution (CV. Inara, 2025)
. Acne vulgaris represents one of the most prevalent dermatological conditions affecting adolescents and young adults, with significant psychosocial consequences including reduced self-esteem and quality of life. Despite the high prevalence of acne among Indonesian adolescents (60-80%), comprehensive investigations examining personal hygiene practices and dietary patterns as modifiable risk factors remain limited. This study aimed to examine the relationship between personal hygiene practices and acne vulgaris severity among medical students at Universitas Prima Indonesia. This descriptive cross-sectional study enrolled 197 medical students from the 2022 cohort using total sampling technique. Data were collected through personal hygiene questionnaires, dietary pattern questionnaires, and clinical acne assessment using the Pillsbury classification system. Statistical analysis employed chi-square tests and Spearman correlation coefficient with significance set at p<0.05. Results demonstrated a statistically significant relationship between personal hygiene practices and acne severity (p=0.000), with respondents maintaining good hygiene exhibiting lower acne grades (34.5% Grade 1) compared to poor hygiene (18.8% Grade 1). Similarly, dietary patterns significantly influenced acne outcomes (p=0.000), with high glycemic index foods and excessive dairy consumption correlating with increased acne severity through hyperinsulinemia and elevated insulin-like growth factor-1. Personal hygiene practices and dietary patterns represent modifiable behavioral factors contributing to acne vulgaris severity in medical students, supporting development of targeted prevention and educational intervention strategies.